Mécanismes De Controle Par La Proximite Et Performance : Cas Specifique Despme Camerounaises Financees Par Capital-Investissement (Global Journal of Management and Business Research, 2021)
SMEs financed by Private equity have this particularity of strong involvement and active partnership of the capital-investor in the different development phases. The purpose aims to measure the effect of the specific control mechanisms as identified in the Cameroonian context on the performance of the financed enterprise. Surveys of SMEs financed, it appears from the multiple regression that the specific disciplinary control mechanisms such as the visits of the agents within the companies, the duration of stay and the activism of the capital-investor to the board of directors have a positive influence on the performance of the financed SME.
Keywords: electronic banking; information technology; digitalization; customers; fintech solutions; local branches